People’s perception on the concept of wadiah in Islamic Banking : a research study on students of UiTM Puncak Alam / Sayyid Umar Syed Ahmad Aljunid - Syed Ahmad Aljunid, Sayyid Umar (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This study aims to identify the perception of the students in UiTM Puncak Alam campus on the concept of wadiah. The study was made to determine if the students understand and know of the wadiah contract, and its concept. The understanding of wadiah is considered to be of importance as it is a part of Islamic finance and is a vital instrument in Islamic banks. Since most UiTM students are Muslims, they should strive to at least appreciate and understand something that can affect their lives in this world and in the Hereafter. The wadiah is exactly that ; an instrument of Islamic banking that can affect their lives even if they do not realise it.